A new pill clam from an unusual habitat: the interstitial Pisidium interstitialis n. sp. (Bivalvia: Sphaeriidae) from southwestern and Central Germany. (28th February 2020) - Groh, Klaus; Bössneck, Ulrich; Clewing, Catharina; Albrecht, Christian; Richling, Ira
Abstract: A new species of pill clam, Pisidium interstitialis n. sp. (Bivalvia: Sphaeriidae), is described from wet meadows bordering a small creek in the Odenwald, southwestern Germany, and from a similar habitat in the Thuringian Schistic Mountains, Central Germany. It can be differentiated from the known European Pisidium species on the basis of shell morphology and DNA sequence data for the mitochondrial cytochrome c oxidase subunit I and 16S rRNA genes. Despite critical evaluation of a large number of potential names from the current synonymies of morphologically similar Pisidium species, no available name was found. Pisidium interstitialis n. sp. is most similar to P. personatum Malm, 1856, and P. casertanum (Poli, 1791), both of which occur syntopically with the new species. Typical specimens of the new species can be readily identified on the basis of shell morphology. However, P. personatum and P. casertanum are morphologically highly variable, so that occasional overlap in conchological characters between these two species and P. interstitialis n. sp. does occur. Although these three taxa co-occur, microhabitat analyses using a special sampling technique showed that P. interstitialis n. sp. exhibits an exclusively interstitial lifestyle, living outside open water bodies. While other Pisidium species may live in the interstitial water of semi-terrestrial habitats, this is the first time that an exclusively interstitial lifestyle has been observed for Pisidium and this may explain why P. interstitialis n. sp. has remained undiscovered for so long. To date, despite the examination of large quantities of Central European samples of Pisidium, the new species is only known from the two areas reported in our study. It seems likely that further surveys will show that P. interstitialis n. sp. has a wider and more continuous distribution.